Pretreatment method of lignocellulose raw material
Through the pretreatment method of combined treatment of acid liquid and steam, the problem of unstable pretreatment effect of lignocellulose raw materials is solved, and more efficient enzymatic saccharification effect is achieved, and the stability of industrial applications is improved.
Patent Information
- Application Number
- CN202311148791.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
The existing pretreatment methods for lignocellulose raw materials are unstable and are greatly affected by differences in raw material composition and impurities, resulting in limited industrial applications.
The lignocellulose raw material is pretreated by combining acid liquid and steam. The specific steps include mixing the lignocellulose raw material with the acid solution, first heating to 100-130°C with steam, then heating to 170-200°C, and pretreatment at appropriate temperatures and pressures.
By optimizing the raw material status and pretreatment process, the enzymatic saccharification effect of lignocellulose raw materials is significantly improved, the pretreatment effect is improved, and the stability of industrial applications is enhanced.
Smart Images

Figure BDA0004436088950000071 
Figure BDA0004436088950000081 
Figure BDA0004436088950000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biological fermentation, and in particular to a pretreatment method for lignocellulose raw materials. Background Art
[0002] Lignocellulosic raw materials are one of the most abundant renewable resources in the world. They have a complex structure and are mainly composed of cellulose, hemicellulose and lignin. Cellulose and hemicellulose can be hydrolyzed and used in the biorefining process based on sugar. However, cellulose is tightly wrapped by the network structure formed by hemicellulose and lignin through covalent bonds, thus forming a stubborn and dense structure. Therefore, before the bioconversion of lignocellulosic raw materials, they must be pretreated to break the network structure of hemicellulose and lignin to expose cellulose, further reduce the degree of polymerization and crystallinity of cellulose, and improve the enzyme accessibility and enzymatic efficiency of cellulose. Therefore, the pretreatment process plays a vital role in the development of the biorefining industry using lignocellulose as raw material.
[0003] At present, the pretreatment methods for lignocellulosic raw materials mainly include physical methods, chemical methods, physicochemical methods and biological methods, including grinding method, alkali treatment method, organic solvent method, wet oxidation method, ammonia fiber expansion method, microwave treatment method, dilute acid pretreatment method, etc. The principles of different pretreatment methods are different, but their main purpose is to remove the structure in the biomass that hinders the binding of cellulase and cellulose during saccharification, reduce the protective effect of lignin or hemicellulose on cellulose, reduce the crystallinity of cellulose crystal structure, increase the specific surface area in the lignocellulosic raw material, make it fully contact with cellulase, and obtain a higher sugar concentration. However, lignocellulosic raw materials are mostly agricultural and forestry wastes, and the raw materials of different batches, different varieties or from different origins have different components. In addition, these raw materials will be mixed with a large number of other material components during the collection and storage process, resulting in significant differences in pretreatment effects with different raw materials. This has become a challenge restricting the industrial application of lignocellulose pretreatment process.
[0004] Therefore, exploring raw materials suitable for pretreatment methods is of great significance to further improve the pretreatment effect. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a method for pretreating lignocellulose raw materials.
[0006] A method for pretreating lignocellulose raw materials, the method comprising: mixing the lignocellulose raw materials with an acid solution, (1) firstly increasing the pressure of the mixed system to 0-0.2 MPa (gauge pressure) by steam, and then increasing the temperature to 100-130°C and maintaining the temperature for 0.5-1 min; (2) continuing to increase the temperature of the mixed system to 170-200°C and the pressure to 0.8-1.6 MPa by steam, and pretreating at the temperature and pressure for 2-10 min.
[0007] In one embodiment, the lignocellulosic raw material includes, but is not limited to, one or more of corn straw, wheat straw, bagasse, rice straw, cotton straw, rape straw, sorghum stalk, wood chips, waste paper, willow branches and jatropha seed shells.
[0008] In one embodiment, the water content of the lignocellulosic raw material is 40wt% or less, further 20wt% or less, and further 15wt% or less. Exemplarily, the water content of the lignocellulosic raw material can be 38wt%, 35wt%, 33wt%, 30wt%, 28wt%, 25wt%, 22wt%, 19wt%, 18wt%, 17wt%, 16wt%, 14wt%, 13wt%, 12wt%, 11wt%, 10wt%, 9wt%, 8wt%, 7wt%, 6wt%, etc.
[0009] In one embodiment, the ash content of the lignocellulosic raw material is 15 wt% or less, further 12 wt% or less, and further 10 wt% or less. Exemplarily, the ash content of the lignocellulosic raw material can be 14 wt%, 13.5 wt%, 13 wt%, 12.5 wt%, 12 wt%, 11.5 wt%, 11 wt%, 10 wt%, 9 wt%, 8.8 wt%, 8 wt%, 7 wt%, etc.
[0010] In one embodiment, the polysaccharide content in the lignocellulosic raw material is 50 wt % or more, further 60 wt % or more.
[0011] In one embodiment, the lignocellulosic feedstock is roughly chopped and freed of particulate matter and dust before being mixed with the acid solution.
[0012] In one embodiment, the rough cutting method includes but is not limited to chopping, grinding, pulverizing, crushing, etc. Rough cutting can be performed using conventional rough cutting equipment in the art.
[0013] In one embodiment, the particle size of the lignocellulosic raw material after rough cutting is 0.1-10 cm, further 0.5-5 cm. For example, the particle size of the lignocellulosic raw material after rough cutting can be 1 cm, 2 cm, 2.5 cm, 3 cm, 4 cm, 6 cm, 7 cm, 8 cm, 9 cm, etc.
[0014] It is generally known to those skilled in the art that the density of particulate matter is generally greater than that of lignocellulosic raw materials. The difference in density between the two can be used to separate the particulate matter from the lignocellulosic raw materials by conventional throwing devices.
[0015] In one embodiment, the granular debris includes sand, gravel, and metal particles.
[0016] In one embodiment, the dust removal method includes manual screening and mechanical screening.
[0017] It is generally known to those skilled in the art that dust in lignocellulosic raw materials mainly comes from dust introduced during the harvesting process and dust generated during the rough cutting process.
[0018] In one embodiment, the mass ratio of the lignocellulosic raw material to the acid solution is 1:(0.1-1.0), further 1:(0.3-0.8).
[0019] In one embodiment, the concentration of the acid solution is 2-10 wt %.
[0020] In one embodiment, the present invention has a wide range of choices for the type of the acid solution, for example, including but not limited to one or more of sulfuric acid solution, hydrochloric acid solution, phosphoric acid solution, nitric acid solution and hydrofluoric acid solution.
[0021] In one embodiment, in step (1), the mixed system is heated to a set temperature (i.e., 100-130° C.), further to 110-120° C., by programmed temperature increase.
[0022] As a preferred embodiment of the present invention, the heating rate in step (1) is controlled to be 10-30°C / min, preferably 15-25°C / min.
[0023] In one embodiment, in step (2), the mixed system is heated to a set temperature (i.e., 170-200° C.), further to 180-190° C.) by programmed temperature increase.
[0024] As a preferred embodiment of the present invention, the heating rate in step (2) is controlled to be 20-50°C / min, preferably 30-45°C / min.
[0025] According to a preferred embodiment of the present invention, the heating rate of step (1) is controlled to be 20-25°C / min, and the heating rate of step (2) is controlled to be 35-40°C / min.
[0026] In one embodiment, the pretreatment time is 3-7 min.
[0027] Compared with the prior art, the present invention has the following technical effects:
[0028] The present invention can improve the pretreatment effect by optimizing the raw material components of the pretreatment and screening out specific raw materials suitable for the pretreatment process; and can further improve the enzymatic saccharification effect by improving the pretreatment process.
[0029] The present invention combines the state of the lignocellulose raw material and the pretreatment process, and optimizes the state of the raw material and the pretreatment process, so as to achieve efficient pretreatment of the lignocellulose raw material and thus improve the pretreatment effect. DETAILED DESCRIPTION
[0030] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the raw materials used can be obtained from commercial channels.
[0031] (1) Enzymatic saccharification evaluation experiment
[0032] The experiment was based on the standard experimental method (LAP-009) of the National Renewable Energy Laboratory (NREL) of the United States with slight adjustments.
[0033] Specifically, 0.5 g of the pretreated material (dry weight) was weighed in a 100 mL conical flask, 10 mL of deionized water was added, and the pH of the enzymatic saccharification system was adjusted to 4.8 with a 5 M NaOH solution, 80 μL of tetracycline solution was added, and the solid content of the enzymatic saccharification system was adjusted to 5% by mass with a 0.1 M pH 4.8 citric acid buffer solution. Then solid cellulase was added, the amount of cellulase was 20 FPU per gram of dry material of lignocellulose raw material (20 FPU / gDM), the enzymatic saccharification temperature was 50 ° C, and the enzymatic saccharification was placed in a water bath shaker at 150 rpm for 72 hours, and then the glucose concentration was measured by sampling.
[0034] Examples 1A to 1E
[0035] The moisture content of corn stover was 15 wt %, the polysaccharide content was 65 wt %, and the ash content was different (see Table 1).
[0036] The corn stalks were roughly chopped to a particle size of 4 cm, and the sand and dust were removed. The corn stalks were then mixed with sulfuric acid solution, and the mass ratio of corn stalks to sulfuric acid solution (concentration of 9wt%) was 1:0.4. (1) The pressure of the mixed system was first increased to 0.07MPa (gauge pressure) by steam at a heating rate of 20℃ / min, and the temperature was raised to 110℃ and maintained for 0.5min; (2) The temperature of the mixed system was continued to be increased to 180℃ and the pressure was increased to 1.5MPa by steam at a heating rate of 40℃ / min, and the pretreatment was carried out at this temperature and pressure for 5min, and the exhaust was exhausted, the pressure was reduced and the temperature was lowered, and the pretreated corn stalks were discharged and cooled for use.
[0037] The pretreated corn stalks were subjected to an enzymatic saccharification evaluation experiment. The results are shown in Table 1.
[0038] Table 1
[0039] Corn stalk ash content (wt%) Glucose concentration in hydrolyzate (g / L) Example 1A 14.68 119.3 Example 1B 11.37 131.4 Example 1C 10.0 136.0 Example 1D 9.45 136.2 Example 1E 7.0 137.0 Comparative Example 1-1 18.03 108.5 Comparative Example 1-2 20.46 102.1
[0040] From the results in Table 1, it can be seen that when the pretreated corn stover is subjected to enzymatic saccharification, it is found that when the ash content is lower than 10wt%, the glucose concentration in the hydrolyzate is above 136g / L; when the ash content is close to about 15wt%, the glucose concentration in the hydrolyzate is lower than 120g / L; when the ash content is higher than 15wt%, the glucose concentration in the hydrolyzate is even lower.
[0041] Examples 2A to 2G
[0042] The corn stover has a polysaccharide content of 60 wt%, an ash content of 9.82 wt%, and different moisture contents (see Table 2).
[0043] The corn stalks were roughly chopped to a particle size of 4.5 cm, and the sand and dust were removed. The corn stalks were then mixed with sulfuric acid solution, and the mass ratio of corn stalks to sulfuric acid solution (concentration of 8 wt%) was 1:0.5. (1) The pressure of the mixed system was first increased to 0.07 MPa (gauge pressure) by steam at a heating rate of 20 °C / min, and the temperature was raised to 110 °C and maintained for 0.5 min; (2) The temperature of the mixed system was continued to be raised to 180 °C and the pressure was raised to 1.5 MPa by steam at a heating rate of 40 °C / min, and the pretreatment was carried out at this temperature and pressure for 5 min, and the corn stalks were exhausted, decompressed and cooled, and the pretreated corn stalks were discharged and cooled for use.
[0044] The pretreated corn stalks were subjected to an enzymatic saccharification evaluation experiment. The results are shown in Table 2.
[0045] Table 2
[0046] Corn stalk moisture content (wt%) Glucose concentration in hydrolyzate (g / L) Example 2A 40.0 122.3 Example 2B 31.2 128.5 Example 2C 20.0 133.2 Example 2D 14.89 137.4 Example 2E 11.08 137.9 Example 2F 8.47 138.7 Example 2G 6.52 139.3 Comparative Example 2-1 45 119.2 Comparative Example 2-2 50 112.4
[0047] From the results in Table 2, it can be seen that when the moisture content of corn stalks is lower than 15wt%, the glucose concentration after stalk hydrolysis is higher than 137g / L; when the moisture content of corn stalks is higher than 40wt%, the glucose concentration after stalk hydrolysis is lower than 120g / L.
[0048] Examples 3A to 3E
[0049] The corn stover had a polysaccharide content of 62 wt%, an ash content of 9.18 wt%, and a water content of 8.61 wt%.
[0050] Corn stalks were roughly chopped into different particle sizes (see Table 3) and sand and dust were removed. Then corn stalks were mixed with sulfuric acid solution, and the mass ratio of corn stalks to sulfuric acid solution (concentration of 8 wt%) was 1:0.5. (1) The pressure of the mixed system was first increased to 0.07 MPa (gauge pressure) by steam at a heating rate of 20 °C / min, and the temperature was raised to 110 °C and maintained for 0.5 min; (2) The temperature of the mixed system was continued to be raised to 180 °C and the pressure was raised to 1.5 MPa by steam at a heating rate of 40 °C / min, and the pretreatment was carried out at this temperature and pressure for 5 min, and the exhaust was exhausted, the pressure was reduced and the temperature was lowered, and the pretreated corn stalks were discharged and cooled for use.
[0051] The pretreated corn stalks were subjected to an enzymatic saccharification evaluation experiment. The results are shown in Table 3.
[0052] Table 3
[0053]
[0054] From the results in Table 3, it can be seen that when the particle size of the corn stalks after coarse cutting is less than 5 cm, the glucose concentration after the stalks are hydrolyzed is greater than 135 g / L; when the particle size of the corn stalks after coarse cutting is greater than 10 cm, the glucose concentration after the stalks are hydrolyzed is lower than 120 g / L. This may be because the particle size is too large and the pretreatment is not thorough, resulting in poor hydrolysis effect.
[0055] Example 4
[0056] The corn stover had a polysaccharide content of 62 wt%, an ash content of 10.55 wt%, and a water content of 9.21 wt%.
[0057] The corn stalks were roughly chopped to a particle size of 4 cm, and the sand and dust were removed. The corn stalks were then mixed with sulfuric acid solution, and the mass ratio of corn stalks to sulfuric acid solution (concentration of 8 wt%) was 1:0.5. (1) The pressure of the mixed system was first increased to 0.07 MPa (gauge pressure) by steam at a heating rate of 20 °C / min, and the temperature was raised to 110 °C and maintained for 0.5 min; (2) The temperature of the mixed system was continued to be increased to 180 °C and the pressure was increased to 1.5 MPa by steam at a heating rate of 40 °C / min, and the pretreatment was carried out at this temperature and pressure for 5 min, and the corn stalks were exhausted, decompressed and cooled, and the pretreated corn stalks were discharged and cooled for use.
[0058] In Comparative Example 4, corn stalks were mixed with sulfuric acid solution, and the temperature of the mixed system was raised to 180° C. and the pressure was raised to 1.5 MPa using steam. The mixture was pretreated at this temperature and pressure for 5 minutes. Other conditions were the same as those in Example 4.
[0059] The pretreated corn stalks were subjected to an enzymatic saccharification evaluation experiment. The results are shown in Table 4.
[0060] Table 4
[0061] Glucose concentration in hydrolyzate (g / L) Example 4 139.2 Comparative Example 4 128.5
[0062] From the results in Table 4, it can be seen that after the corn stalks were pretreated by staged heating, the glucose concentration in the hydrolyzate was relatively high, reaching 139.2 g / L. However, after the direct heating pretreatment in Comparative Example 4, the glucose concentration in the hydrolyzate was relatively low, at 128.5 g / L.
[0063] Examples 5A to 5E
[0064] The corn stover has a polysaccharide content of 65 wt%, an ash content of 10.01 wt%, and a water content of 7.3 wt%.
[0065] The corn stalks were roughly chopped to a particle size of 3.5 cm, and the sand and dust were removed. The corn stalks were then mixed with sulfuric acid solution, and the mass ratio of corn stalks to sulfuric acid solution (concentration of 8 wt%) was 1:0.7. (1) The pressure of the mixed system was first increased to 0.07 MPa (gauge pressure) by steam, and the temperature was increased to 110°C and maintained for 0.5 min; (2) The temperature of the mixed system was continued to be increased to 180°C and the pressure was increased to 1.5 MPa by steam, and pretreated at this temperature and pressure for 5 min, exhausted, reduced pressure and cooled, and the pretreated corn stalks were discharged and cooled for use.
[0066] Among them, in Examples 5A to 5E and Comparative Example 5, the heating rates of steps (1) and (2) are different (see Table 5).
[0067] The pretreated corn stalks were subjected to an enzymatic saccharification evaluation experiment. The results are shown in Table 5.
[0068] Table 5
[0069]
[0070]
[0071] From the results in Table 5, it can be seen that after the corn stalks were pretreated at different heating rates, it was found that when the heating rate in step (1) was 10-30°C and the heating rate in step (2) was 20-50°C, the glucose concentration in the hydrolyzate reached more than 130 g / L. By further optimizing the heating rate, the glucose concentration in the hydrolyzate would be higher. However, when the corn stalks were pretreated by the heating method of Comparative Example 5, the glucose concentration in the hydrolyzate was only 127.4 g / L.
[0072] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for pretreating lignocellulosic raw materials, characterized in that: The method comprises: mixing a lignocellulose raw material with an acid solution; (1) firstly increasing the pressure of the mixed system to 0-0.2 MPa (gauge pressure) by steam, and then increasing the temperature to 100-130° C. and maintaining the temperature for 0.5-1 min; and (2) continuing to increase the temperature of the mixed system to 170-200° C. and the pressure to 0.8-1.6 MPa by steam, and pretreating at the temperature and pressure for 2-10 min.
2. The method for pretreating lignocellulosic raw materials according to claim 1, characterized in that: The lignocellulosic raw materials include but are not limited to one or more of corn straw, wheat straw, bagasse, rice straw, cotton straw, rape straw, sorghum stalk, wood chips, waste paper, switch twigs and jatropha seed shells; and / or, The water content of the lignocellulosic raw material is 40 wt% or less, further 20 wt% or less, and further 15 wt% or less.
3. The method for pretreating lignocellulosic raw materials according to claim 1, characterized in that: The ash content of the lignocellulosic raw material is 15 wt % or less, further 12 wt % or less, and further 10 wt % or less.
4. The method for pretreating lignocellulosic raw materials according to claim 1, characterized in that: The polysaccharide content in the lignocellulose raw material is 50 wt% or more, and further 60 wt% or more.
5. The method for pretreating lignocellulosic raw materials according to claim 1, characterized in that: Before mixing the lignocellulosic raw material with the acid solution, it is first roughly chopped and freed from particulate matter and dust; Furthermore, the rough cutting method includes chopping, grinding, pulverizing and crushing.
6. The method for pretreating lignocellulosic raw materials according to claim 5, characterized in that: The particle size of the roughly chopped lignocellulose raw material is 0.1-10 cm, and further 0.5-5 cm.
7. The method for pretreating lignocellulosic raw materials according to claim 1, characterized in that: The mass ratio of the lignocellulose raw material to the acid solution is 1:(0.1-1.0), further 1:(0.3-0.8).
8. The method for pretreating lignocellulosic raw materials according to claim 1, characterized in that: The concentration of the acid solution is 2-10 wt %, and / or the acid solution includes one or a combination of sulfuric acid solution, hydrochloric acid solution, phosphoric acid solution, nitric acid solution, and hydrofluoric acid solution.
9. The method for pretreating lignocellulosic raw materials according to claim 1, characterized in that: In step (1), the mixed system is heated to a set temperature in a programmed temperature-raising manner, further 110-120° C.; preferably, the heating rate is controlled to be 10-30° C. / min, more preferably 15-25° C. / min; And / or, in step (2), the mixed system is continued to be heated to a set temperature in a programmed temperature manner, further 180-190°C; preferably, the heating rate is controlled to be 20-50°C / min, more preferably 30-45°C / min.
10. The method for pretreating lignocellulosic raw materials according to claim 1, characterized in that: The pretreatment time is 3-7 minutes.